2015
DOI: 10.1016/j.procs.2015.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship between Systems Engineering and Software Engineering

Abstract: In an effort to explore the relationship between the disciplines of systems engineering and software engineering, professionals from academia, industry, and government gathered for a workshop to deliberate on the current state, to acknowledge areas of inter-dependence, to identify relevant challenges, and to propose recommendations for addressing those challenges with respect to four topical areas: 1) Development Approaches, 2) Technical, 3) People, and 4) Education. This paper presents the deliberations and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 2 publications
0
16
0
Order By: Relevance
“…In recent years, INCOSE 2 has promoted an empirical approach to tackle the problems between these two disciplines. For instance, Pyster et al [35] reported on a workshop co-sponsored by INCOSE with 29 professionals from academia and industry described as a "cross section of systems and software engineering community", held to identify said problems, and the challenges created by them. Subsequently, INCOSE approved the charter of the Systems and Software Interface Working group (SaSIWG), and recently published a series of problem-related findings identified through its members interaction [39,40].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, INCOSE 2 has promoted an empirical approach to tackle the problems between these two disciplines. For instance, Pyster et al [35] reported on a workshop co-sponsored by INCOSE with 29 professionals from academia and industry described as a "cross section of systems and software engineering community", held to identify said problems, and the challenges created by them. Subsequently, INCOSE approved the charter of the Systems and Software Interface Working group (SaSIWG), and recently published a series of problem-related findings identified through its members interaction [39,40].…”
Section: Related Workmentioning
confidence: 99%
“…mechanical, electronic) constituent systems. However, software is now not only pervasive and abundant, but also a critical element of the performance and features offered by most modern engineered systems [17,35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the scientific community, BOK allows for the widening of the spectrum of research fields based on consensus and highlights similarities between disciplines [65]. For example, BOK highlights techniques used in materials science that are common between chemistry and physics [66].…”
Section: Open Bok Contextmentioning
confidence: 99%
“…The authors noticed the lack of holistic considerations within SWE in general, especially when the software engineers are not educated in SE. What is interesting according to Pyster et. Al.…”
Section: Introductionmentioning
confidence: 98%